POSTOPERATIVE COMPLICATIONS IN EMERGENCY VERSUS ELECTIVE LAPAROTOMIES AT A PERIPHERAL HOSPITAL - Murtaza, Badar; Saeed, Saira; Sharif, Muhammad Ashraf (Journal of Ayub Medical College Abbottabad, 2010)
Background: Laparotomy is a commonly performed procedure in any surgical unit. Postoperative complications directly affect the outcome of the disease. The aim of the study was to evaluate and compare the postoperative complications in emergency versus elective laparotomies at a peripheral hospital. Methods: This comparative cross-sectional study was carried out at the Department of General Surgery, Combined Military Hospital, Bahawal Nagar Cantonment from Feb 2006 to May 2009. One hundred and four consecutive patients undergoing laparotomy were included. They were divided into two groups: emergency laparotomies (Group-A) and elective laparotomies (Group-B). They were followed up meticulously and the postoperative complications/sequel were recorded. Results: In Group-A there were 83 patients while in GroupB only 21 patients were recorded. A total of 73 postoperative complications were seen in 28 patients (33.7%) in Group-A, while 5 complications were seen in 3 patients (14.2%) in Group-B. The Group-A showed 21.6% postoperative fever and wound infection, postoperative nausea and vomiting was 13.2%, wound dehiscence 4.8%, incisional hernia 3.6%, pneumonia/anastomotic disruption 2.4% and duodenal fistula/peristomal excoriation/adhesive intestinal obstruction 1.2%. The septicaemia was seen in 6.0% and mortality in 8.4%. Group B showed 14.2% postoperative fever and 4.7% postoperative nausea and vomiting/wound infection. No case of septicaemia or mortality was seen. Conclusion: The postoperative complications are more common in emergency laparotomies as compared to the elective ones. Postoperative fever, wound infection, nausea and vomiting are the mostly encountered complications. Keywords: Laparotomy, emergency, elective, postoperative, complications